FRI0492 Ultrasound study of entheses in psoriasis patients with or without musculoskeletal disease: a prospective study. (23rd January 2014) - Albert, C.; Montaudie, H.; Acquacalda, E.; Fontas, E.; Danre, A.; Roux, C. H.; Breuil, V.; Passeron, T.; Euller-Ziegler, L.
Abstract : Background: The use of ultrasonography (US) can be of interest in the diagnosis and the follow-up of enthesitis, notably in SA. In recent studies asymptomatic US enthesitis were more frequently observed in psoriasis patients (pts) than in controls. Objectives: 1/ To estimate the prevalence of US enthesitis in psoriasis pts with or without musculoskeletal symptoms 2/ To assess by US imaging the evolution of enthesitis with systemic treatment (TT). Methods: Prospective bi-centre (rheumatology & dermatology) study over 6 months including Psoriasis pts requiring systemic TT, with or without musculoskeletal symptoms and psoriatic arthritis (PsA, according to CASPAR criteria). Clinical assessment (M0 M3 M6) included: BASDAI, HAQ, SPARCC, PASI, nail disease and comorbidities. US assessment (M0 M6) Grey Scale (GS) Power Doppler (PD) of 10 entheses, by a trained rheumatologist blinded to other data, scoring (absent/present) morphology (thickening and hypoechogenicity), structure and PD signal. Statistical analysis: test of Chi ² (data at baseline) ; test for series matched by Wilcoxon and Chi ² of Mc Nemar (analysis M0 M6). Results: 340 entheses were studied in 34 pts, 22 asymptomatic and 12 PsA (fulfilling CASPAR criteria), mean age 43.5 years, mean psoriasis duration 15.9 years, mean BASDAI=48.1, mean PASI=15.9, mean CRP=4.2 mg/l. 23 patients received acitretin or methotrexate (MTX) or ciclosporin and 11 pts received anti TNF. At baseline: US abnormalities in 97.1% total population and in 86.4% psoriasis pts. 95/340 enthesitis, 57/220 in asymptomatic pts vs 38/120 in PsA (p = 0, 258). Neither group had PD signal. 24/90 enthesitis in pts with nail disease (n=9) vs 33/130 without (n=13) (p = 0, 831). 23 pts were assessed at M6, receiving MTX (n=12) and anti TNF (n=11). Improving US morphological abnormalities both in asymptomatic pts (n=13) (p=0, 021) and PsA (n=10) (p= 0, 164). Significant decrease of BASDAI, HAQ, SPARCC. Conclusions: Discussion : According to the series, asymptomatic US enthesitis was reported in 11% to 32 % of psoriasis pts compared with the control (1, 2 ). In our study, US enthesitis were observed in 86.4 % of the psoriasis pats, possibly due to a severe psoriasis in our population, all requiring systemic TT (inclusion criteria). In patients with nail disease, we did not observe the previously reported higher frequencies of US enthesitis (3, 4 ), because only a few had nail disease. Previous studies of US-detected enthesitis have demonstrated a good response to change under SA TT, with a decrease in PD signal. To our knowledge, our study is the first to show an improvement of US entheseal morphological abnormalities in psoriasis pts after systemic TT. Conclusion : We observed a high frequency of US enthesitis in pts with severe psoriasis requiring systemic TT with or without musculoskeletal symptoms. These US morphological abnormalities are likely to improve after 6months of systemic TT. Further studies would be interesting to validate data and to estimate the predictive value of asymptomatic US enthesitis in psoriasis pts. References: Naredo E. et al. Rheumatology (Oxford). 2011 ; Gutierrez M. et al. Semin Arthritis Rheum. 2011 ; Ash ZR et al.Ann Rheum Dis. 2012 ; Aydin SZ et al. Ann Rheum Dis. 2012. Disclosure of Interest: None Declared